حقوق الأشخاص ذوي الإعاقة في القانون الكويتي : دراسة تأصيلية تطبيقية في ضوء مقاصد الشريعة - علي، فاطمة أحمد محمد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The study sheds light on the rights of persons with disabilities in Islamic and Kuwaiti law. It extensively deals with the concept of disability, the diversity and the scope of the concept. The researcher presented their fundamental rights, and sociopolitical, health and financial rights in Islamic law. These are amongst the crucial issues in the life of the disabled persons, especially when there is widespread ignorance in some segments of society about their rights. Yet some others belittle them, make fun of their personality and entity, neglect their dignity, exploit their weakness and little resources as they have. The study also explained their rights in Kuwaiti law and the extent of importance the Kuwaiti law put in the affairs of the disabled. It gives prime importance on Maqasidic [shari'ah objectives] approach to safeguard and protect their rights; the Maqasidic principles that clarify the stand of Islamic law towards the disabled, take care of them and lessen their burdens. The last chapter exposes the effectiveness of the law of disabled people in Kuwait, its application and the shortcoming that it faces. The chapter also presents the role of the developed countries and how do they care for their disabled citizen in order to benefit from their experineces to improve the Kuwaiti laws in its care for the disabled. The study follows inductive method by exploring the Shari'ah evidence in ancient and contemporary legal and sociological references, in Rules, Regulations and Articles of Kuwaiti Law. It also adopts analytical method to analyze the religious texts and legal evidence, statements of scholars. It also uses the comparative method to get hold of comparative methodological texts to explore points of agreement and disagreement between Maqasid Shari'ah and Kuwaiti Law. The study highlighted some important conclusions, including; justice of Islamic law in the field, and its protection of the rights of the disabled; and that the Kuwait is considered to be among the pioneers in the care of the disabled; but the absence of proper implementation of the law adversely affected the disabled beneficiaries to enjoy their legal rights.